Patient-Specific Variations in Local Strain Patterns on the Surface of a Trussed Titanium Interbody Cage - Loenen, Arjan C. Y.; Noailly, Jérôme; Ito, Keita; Willems, Paul C.; Arts, Jacobus J.; van Rietbergen, Bert (Frontiers in Bioengineering and Biotechnology, 2022)
Introduction: 3D printed trussed titanium interbody cages may deliver bone stimulating mechanobiological strains to cells attached at their surface. The exact size and distribution of these strains may depend on patient-specific factors, but the influence of these factors remains unknown. Therefore, this study aimed to determine patient-specific variations in local strain patterns on the surface of a trussed titanium interbody fusion cage. Materials and Methods: Four patients eligible for spinal fusion surgery with the same cage size were selected from a larger database. For these cases, patient-specific finite element models of the lumbar spine including the same trussed titanium cage were made. Functional dynamics of the non-operated lumbar spinal segments, as well as local cage strains and caudal endplate stresses at the operated segment, were evaluated under physiological extension/flexion movement of the lumbar spine. Results: All patient-specific models revealed physiologically realistic functional dynamics of the operated spine. In all patients, approximately 30% of the total cage surface experienced strain values relevant for preserving bone homeostasis and stimulating bone formation. Mean caudal endplate contact pressures varied up to 10 MPa. Both surface strains and endplate contact pressures varied more between loading conditions than between patients. Conclusions: This study demonstrates the applicability of patient-specific finite element models to quantify the impact of patient-specific factors such as bone density, degenerative state of the spine, and spinal curvature on interbody cage loading. In the future, the same framework might be further developed in order to establish a pipeline for interbody cage design optimizations.